Various Modalities Accurate in Diagnosing a Disrupted or Disconnected Pancreatic Duct in Acute Pancreatitis: A Systematic Review - Timmerhuis, Hester C. (Dig Dis Sci, 2020)
BACKGROUND: Severe pancreatitis may result in a disrupted pancreatic duct, which is associated with a complicated clinical course. Diagnosis of a disrupted pancreatic duct is not standardized in clinical practice or international guidelines. We performed a systematic review of the literature on imaging modalities for diagnosing a disrupted pancreatic duct in patients with acute pancreatitis. METHODS: A systematic search was performed in PubMed, Embase and Cochrane library databases to identify all studies evaluating diagnostic modalities for the diagnosis of a disrupted pancreatic duct in acute pancreatitis. All data regarding diagnostic accuracy were extracted. RESULTS: We included 8 studies, evaluating five different diagnostic modalities in 142 patients with severe acute pancreatitis. Study quality was assessed, with proportionally divided high and low risk of bias and low applicability concerns in 75% of the studies. A sensitivity of 100% was reported for endoscopic ultrasound and endoscopic retrograde cholangiopancreatography. The sensitivity of magnetic resonance cholangiopancreatography with or without secretin was 83%. A sensitivity of 92% was demonstrated for a combined cohort of secretin-magnetic resonance cholangiopancreatography and magnetic resonance cholangiopancreatography. A sensitivity of 100% and specificity of 50% was found for amylase measurements in drain fluid compared with ERCP. CONCLUSIONS: This review suggests that various diagnostic modalities are accurate in diagnosing a disrupted pancreatic duct in patients with acute pancreatitis. Amylase measurement in drain fluid should be standardized. Given the invasive nature of other modalities, secretin-magnetic resonance cholangiopancreatography or magnetic resonance cholangiopancreatography would be recommended as first diagnostic modality. Further prospective studies, however, are needed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10620-020-06413-0) contains supplementary material, which is available to authorized users.